How Are We Facing It? Dispatches From Pathology Residents in a COVID-19 Lombardy Hospital - Cieri, Miriam; De Carlo, Camilla; Valeri, Marina; Belsito, Vincenzo; Lancellotti, Cesare; Roncalli, Massimo; Colombo, Piergiuseppe (Frontiers in Public Health, 2020)
At the end of February, the Italian National Health Service reported a hot spot of Coronavirus disease in the Lombardy region. COVID-19 is a highly pathogenic viral infection which poses some challenges for healthcare workers. Indeed, Pathology Departments are involved in reorganizing samples' management, from their delivery until their processing, according to National and WHO guidelines. Since Lombardy has been declared COVID-19 hot spot, due to decreasing number of surgical procedures, our Department adopted a policy to reduce personnel, allowing pathologists to work remotely during the outbreak. Lacking clear information about viral load on tissue samples, all human specimens must be considered potentially infectious, as well as patients during post-mortem examinations, and clinical information on COVID-19 status is mandatory. It is also important that Pathology staff receive an adequate training, and adherence to rules should be always accompanied by common sense.